You need to combine the different parts that contain the variable "a". Just add the coefficients together algebraically.
The idea here is to combine terms that have the same variable (or, in more complicated cases, the same combination of variables). For example, 3a + 2a is the same as 5a.
-4 + 10 + 6a - 2a + 3 9 + 4a
2a*4b*(-3c) = ? 2 * 4 * -3 * a * b * c = ? -24abc
4
It is 14x+4 simplified
7a + 4 = 5a + 7 7a = 5a + 3 2a = 3 a = 3/2
2a + 3a + 4 = 5a + 4
5a + 3 = 7a - 1 add 1 to both sides 5a + 4 = 7a so 4 = 2a as 5a + 2a = 7a 4 = 2a = 2 x 2 so a = 2 Check: then 5a + 3 = 10 + 3 = 13 and 7a - 1 = 14 - 1 = 13
7
2a-8+4=45-5a 2a-4=45-5a 2a-4+4=45+4-5a 2a+5a=49-5a+5a 7a=49 / by 7 = A=7
The idea here is to combine terms that have the same variable (or, in more complicated cases, the same combination of variables). For example, 3a + 2a is the same as 5a.
2a + 3 - 9b - a - 7 Bring like terms together: = 2a - a - 9b + 3 - 7 Combine like terms: = a - 9b - 4
It looks like you've taken 'a' away from '7a' three times, so you probably have 4 of them left.
7a
555
-4 + 10 + 6a - 2a + 3 9 + 4a
a/7 + a/4 = 4a/28 + 7a/28 = 11a/28